2007
DOI: 10.1007/s10820-006-9038-5
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic properties of the water/amorphous silica interface: a model for the undissociated surface

Abstract: Amorphous silica-water interfaces are found ubiquitously in nanoscale devices, including devices fabricated from silica as well as from silicon that acquire a surface oxide layer. The surface silanol groups serve as hydrogen-bonding sites for a variety of chemical species, and their reactivity enables convenient chemical modification, making silica surfaces strategic in bio-sensing applications. We have extended the popular BKS and SPC/E models for bulk silica and water to describe the hydrated, hydroxylated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…This would not only remove our reliance on empirical force fields, but also provide a general methodology for handling rough and atomically-detailed surfaces (anisotropic geometries). Research into such methods has already demonstrated success, [149][150][151][152] but the associated computational expense limits the data to relatively short (sub-nanosecond) trajectories. As advances in computer technology and algorithms continues to progress and we are able to get an increasinglyrefined view of interfacial water structure, the next frontier would be to provide the same detailed treatment for ions, surfactants, and large solutes as peptides and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This would not only remove our reliance on empirical force fields, but also provide a general methodology for handling rough and atomically-detailed surfaces (anisotropic geometries). Research into such methods has already demonstrated success, [149][150][151][152] but the associated computational expense limits the data to relatively short (sub-nanosecond) trajectories. As advances in computer technology and algorithms continues to progress and we are able to get an increasinglyrefined view of interfacial water structure, the next frontier would be to provide the same detailed treatment for ions, surfactants, and large solutes as peptides and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Na Cl (28) either from the PB equations or from an MD trajectory. Equations 26 and 27 match the total number of ions and total ion charge, respectively, between MD and the PB theory in the region |z| < z d .…”
Section: ∫ ∫mentioning
confidence: 99%
“…In recent years, forcefield based simulation techniques have been developed and applied in order to model the oxide/water interface,123–149 especially the TiO 2 ‐water interface 96, 150–155. The interaction of transition metal oxide surfaces with water, including dissolution and inorganic/organic species adsorption, is now being described.…”
Section: State Of Artmentioning
confidence: 99%